2008
DOI: 10.1002/biot.200700252
|View full text |Cite
|
Sign up to set email alerts
|

Glycoengineering of the methylotrophic yeast Hansenula polymorpha for the production of glycoproteins with trimannosyl core N‐glycan by blocking core oligosaccharide assembly

Abstract: The initial lipid-linked oligosaccharide Glc(3)Man(9)GlcNAc(2)-dolichyl pyrophosphate (Dol-PP) for N-glycan is synthesized and assembled at the membrane of the endoplasmic reticulum (ER) and subsequently transferred to a nascent polypeptide by the oligosaccharide transferase complex. We have identified an ALG3 homolog (HpALG3) coding for a dolichyl-phosphate-mannose dependent alpha-1,3-mannosyltransferase in the methylotrophic yeast Hansenula polymorpha. The detailed analysis of glycan structure by linkage-spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…Interestingly, the N-glycosylation pathway of H. polymorpha has been remodeled by deleting the HpALG3 gene in the Hpoch1 null mutant strain and blocked in the yeastspecific outer mannose chain synthesis and by introducing an ER-targeted Aspergillus saitoi -1,2-mannosidase gene. This glycoengineered H. polymorpha strain produced glycoproteins mainly containing trimannosyl core N-glycan (Man3GlcNAc2), which is the common core backbone of various human-type N-glycans and the glycoform is the same as that of Cerezyme which was achieved through in vitro sequential deglycosylation of complex glycans (Oh et al, 2008). Similar glycoengineering effort was published in a glycoengineered Pichia with the ability of producing glycoprotein carrying similar mannose type of glycan .…”
Section: Glycosylation On Recombinant Human Glucocerebrosidase Is Crimentioning
confidence: 88%
“…Interestingly, the N-glycosylation pathway of H. polymorpha has been remodeled by deleting the HpALG3 gene in the Hpoch1 null mutant strain and blocked in the yeastspecific outer mannose chain synthesis and by introducing an ER-targeted Aspergillus saitoi -1,2-mannosidase gene. This glycoengineered H. polymorpha strain produced glycoproteins mainly containing trimannosyl core N-glycan (Man3GlcNAc2), which is the common core backbone of various human-type N-glycans and the glycoform is the same as that of Cerezyme which was achieved through in vitro sequential deglycosylation of complex glycans (Oh et al, 2008). Similar glycoengineering effort was published in a glycoengineered Pichia with the ability of producing glycoprotein carrying similar mannose type of glycan .…”
Section: Glycosylation On Recombinant Human Glucocerebrosidase Is Crimentioning
confidence: 88%
“…Several yeast and fungal species have been used in the development of secretion hosts producing therapeutic glycoproteins with human complex-type N-glycans (15,16,33). Recently, pioneering work on the engineering of the O-glycosylation pathway expressing human proteins in S. cerevisiae was reported (8).…”
Section: Discussionmentioning
confidence: 99%
“…Yeast cells were routinely grown in YPD medium (1% Bacto yeast extract, 2% Bacto peptone, 2% glucose) or synthetic complete (SC) medium (0.67% yeast nitrogen base without amino acids, 2% glucose, dropout amino acid mixture supplemented with all required amino acids). Hphac1 and Hpire1 deletion mutants were constructed in the H. polymorpha DL1-L background by fusion PCR and in vivo DNA recombination (15), using the primer sets listed in Table 1. PCR fragments were introduced into yeast cells, and the transformants carrying the gene deletion as a result of in vivo DNA recombination were selected first by growth in minimal medium lacking leucine (SC-LEU) and then by PCR screening.…”
Section: Methodsmentioning
confidence: 99%
“…7B). To confirm the positive effect of HpHac1p on the modulation of glycosylation, we performed the same experiment employing the Hpalg3⌬ mutant strain, which has a defect in the conversion step of Man 5 GlcNAc 2 -dolichyl pyrophosphate (Dol-PP) to Man 6 GlcNAc 2 -Dol-PP in the ER (15). Our previous study reported that the S. cerevisiae CPY protein was hypoglycosylated with a reduced extent of occupancy at N-glycosylation sites in the Hpalg3⌬ mutant (13).…”
Section: Expression Of Hphac1mentioning
confidence: 98%
See 1 more Smart Citation